2016
DOI: 10.1080/02678373.2016.1252971
|View full text |Cite
|
Sign up to set email alerts
|

Work stress and alcohol use: developing and testing a biphasic self-medication model

Abstract: This study developed and tested a moderated-mediation model of work stress and alcohol use, based on the biphasic (stimulant and sedative) effects of alcohol and the self-medication and stress-vulnerability models of alcohol use. The model proposes that exposure to work stressors can increase both negative affect and work fatigue, and that these two sources of strain can subsequently motivate the use of alcohol. However, the relations of negative affect and work fatigue to alcohol use are conditional on the jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 60 publications
(88 reference statements)
3
59
0
4
Order By: Relevance
“…Two main mechanisms of how psychosocial work factors specifically impact alcohol use have been previously proposed: the tension-reduction model35 and the biphasic self-medication model 13. The tension-reduction model suggests that alcohol use is a coping mechanism to reduce negative feelings that occurs from experiencing work stressors 14 35.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two main mechanisms of how psychosocial work factors specifically impact alcohol use have been previously proposed: the tension-reduction model35 and the biphasic self-medication model 13. The tension-reduction model suggests that alcohol use is a coping mechanism to reduce negative feelings that occurs from experiencing work stressors 14 35.…”
Section: Discussionmentioning
confidence: 99%
“…The tension-reduction model suggests that alcohol use is a coping mechanism to reduce negative feelings that occurs from experiencing work stressors 14 35. This theory has been expanded by Frone13 in the biphasic self-medication model, which suggests that individuals consume alcohol to mitigate the impact of negative affect (feelings of emotional distress, anxiety or irritability) and work fatigue caused by work exposures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study observed that 12% of employees from a representative sample of the Québec population started to misuse alcohol during a 8‐year follow‐up after entering employment . Drinking to cope with work stress was postulated to be a contributing factor for problem drinking in workers, and long working hours has been one of the most studied psychosocial work stressors.…”
Section: Introductionmentioning
confidence: 99%